PERBANDINGAN SELF AWARENESS ANTARA PESERTA DIDIK PEROKOK DAN NON-PEROKOK - Mukhammad Ryan Putra Ardhani; Wiryo Nuryono Nuryono (IKIP Siliwangi, 2026)
Smoking behavior among students is often associated with low self-awareness, although this assumption has not been fully supported by empirical evidence. This study is important to objectively examine differences in self-awareness levels between smoking and non-smoking students. The purpose of this study was to compare self-awareness levels between the two groups. This research employed a quantitative comparative method with a cross-sectional design and an ex post facto approach. The participants consisted of 44 students, including 22 smokers and 22 non-smokers selected through random sampling. The research instruments included a self-awareness scale and the Cigarettes Dependence Scale (CDS-12). Data analysis was conducted using validity and reliability tests, descriptive analysis, normality tests, and an Independent Samples t-test. The results indicated that there was no significant difference in self-awareness levels between smoking and non-smoking students based on the Independent Samples t-test (t = −1.079; p = 0.287) These findings suggest that smoking behavior does not directly reflect students’ level of self-awareness. Therefore, guidance and counseling services in schools should consider factors beyond self-awareness in efforts to prevent smoking behavior among students.